2017
DOI: 10.3390/nu9060555
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of the Anti-Inflammatory Effects of Probiotics and Synbiotics in Intestinal Chronic Diseases

Abstract: Probiotics and synbiotics are used to treat chronic diseases, principally due to their role in immune system modulation and the anti-inflammatory response. The present study reviewed the effects of probiotics and synbiotics on intestinal chronic diseases in in vitro, animal, and human studies, particularly in randomized clinical trials. The selected probiotics exhibit in vitro anti-inflammatory properties. Probiotic strains and cell-free supernatants reduced the expression of pro-inflammatory cytokines via act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
201
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 322 publications
(215 citation statements)
references
References 74 publications
11
201
0
3
Order By: Relevance
“…However, more prolonged DEPs exposure reduced the abundance of Lactobacillus in the gut microbiota, which may have contributed to damage to the colonic epithelium. [29] Therefore, our results suggest that supplementation of the diet with probiotics may provide some protection against DEPs-related colonic injury. Lactobacillus is one of the commonly used probiotics in commercial products.…”
Section: Discussionmentioning
confidence: 69%
“…However, more prolonged DEPs exposure reduced the abundance of Lactobacillus in the gut microbiota, which may have contributed to damage to the colonic epithelium. [29] Therefore, our results suggest that supplementation of the diet with probiotics may provide some protection against DEPs-related colonic injury. Lactobacillus is one of the commonly used probiotics in commercial products.…”
Section: Discussionmentioning
confidence: 69%
“…It has been demonstrated that probiotics can affect the structure of gut microbiota and the interaction with the microbial community and the host health through different mechanisms [12,[193][194][195]. These effects are mediated by the direct or indirect action of probiotics and can involve the modulation of the immune system or that of remote organs like the brain and liver due to the production of metabolites finally localized in these organs [193,[196][197][198][199].…”
Section: Probiotic Administration Microbiota Bile Acids and Cardiovmentioning
confidence: 99%
“…Probiotics are currently defined as nonpathogenic microorganisms and have been reported to improve metabolic diseases such as obesity and diabetes through modulation of intestinal microorganisms [17,18]. Their beneficial health effects could be attributed to their antiinflammatory and immunoregulatory properties [19]. Some probiotic strains were shown to induce significant antioxidant activity through action on superoxide dismutase (SOD), catalase (CAT) and glutathione peroxidase (GPx) [20].…”
Section: Introductionmentioning
confidence: 99%